PELUANG DAN TANTANGAN INVESTASI PROPERTI DI INDONESIA - Hidayat, Rony Wahyu (Jurnal Akuntansi AKUNESA, 2014)
Investmen is something to invest to other instruments by expecting to get profits in the future. One of the investment which gets profit is an invesment property.The investment property such as land, bulidings which can be rented. Beside that, invesment property business also will get opportunities and challenge, the opportunities of the property price has incrased every year. So, that bussiness has ensured profits.Keywords : Investment, investment properties